Failure analysis of center cutter mount in shield machine under tuff layer. (November 2020) - Ning, Bo; Liu, Hao; Cui, Jianbo; Xia, Yimin; Lin, Laikuang; Zhao, Shifang; Fu, Jie
Highlights: We researched on the fracture failure by analyzing the damaged components of the center cutter mount. We investigated the stress distribution and fatigue life of the center cutter mount. Some suggestions were given to improve the lifetime of the center cutter mount. Abstract: The shield machine is a giant dedicated engineering machine used for digging the full section of a tunnel. During the railway tunnel construction in Jinan through tuff layer, the fasteners of the center cutter in a large number of EPB shield machines, used in the construction, encountered fracture failure. In this paper, investigating the failure morphology of the failed components in the construction site, the reason of such fracture failure is found to be the fatigue failure under the low-frequency impact load. The finite element method is employed here to investigate the stress distribution and deformation status of the fastener when the center cutter mount of the shield machine is under the static load. Results show that the sliding dislocation of the joint surface between the wedge and cutter under the preload will significantly reduce the lifetime of the fastener. We used the multi-functional rock-breaking platform of the Central South University to perform the full-scale experiment of rock-breaking by the cutter and obtained the complex load caused by the coupling of the cutter and the rock. By taking the load as the input, we analyzed the fatigue life of the bolt under different preloads. We suggest that during the tuff layer construction, the center cutter mount can reach the expected lifetime of the bolt by properly reducing the bolt preload under the sufficient and reliable anti-loose condition of the bolt.